Evaluating the Effectiveness of the Quality Management Program at Dompet Dhuafa Using the CIPP Model - Ahmad Juwaini; Leis Suzanawaty (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Islamic philanthropic institutions face increasing demands for transparency, accountability, and operational efficiency to meet the expectations of donors and beneficiaries. To address these challenges, Dompet Dhuafa implemented a quality management program in 2013 aimed at improving organizational performance and service delivery. Despite the widespread adoption of quality management systems, few studies have systematically evaluated their effectiveness and sustainability in Islamic philanthropic organizations, creating a research gap. This study evaluates the quality management program using the Context, Input, Process, Product (CIPP) evaluation model, assessing its relevance, resource adequacy, conformity to planned processes, and outcomes. Data were collected through participant observation, interviews, documentation, questionnaires, and focus group discussions. Analysis reveals that the program is highly aligned with organizational needs, receives moderate input support, demonstrates moderate conformity to planned processes, and achieves high levels of effectiveness, efficiency, responsiveness, and sustainability. These results indicate that structured quality management enhances organizational performance, strengthens accountability, increases stakeholder trust, and supports long-term institutional sustainability. The study underscores the importance of leadership commitment, dedicated human resources, adequate budgeting, and continuous monitoring for maintaining and replicating quality management practices in similar Islamic philanthropic organizations.